New genus and species of Selenopidae (Arachnida, Araneae) from Madagascar and neighbouring islands - Corronca, Jose Antonio (2003)
A new spider genus, Garcorops, in the family Selenopidae is described from Madagascar and the Comoro Islands based on the type species Garcorops madagascar n.sp. (male and female). Two additional new species included in this genus are described and illustrated, namely G. jocquei (female only) from the Comoros and G. paulyi (female only) from Madagascar.